2012
DOI: 10.1210/jc.2011-3253
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Taspoglutide in Patients with Type 2 Diabetes Inadequately Controlled with Metformin Plus Pioglitazone over 24 Weeks: T-Emerge 3 Trial

Abstract: Objective: This study assessed the efficacy and safety of once-weekly taspoglutide in patients with type 2 diabetes mellitus inadequately controlled with metformin plus pioglitazone compared with placebo. Design:In this randomized, double-blind, parallel-group, placebo-controlled trial (T-emerge 3), 326 patients were randomized to once-weekly sc injections of taspoglutide 10 mg, taspoglutide 20 mg (10 mg for first 4 wk), or placebo. The primary endpoint was change from baseline in glycosylated hemoglobin (HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
(22 reference statements)
2
27
0
Order By: Relevance
“…The beneficial waist circumference reduction effect associated with GLP-1RAs observed in our analysis was consistent with relevant trials [36,37,42,43]. A study in 299 T2DM patients showed a significant decrease in waist circumference associated with exenatide accompanied by significant weight loss [42].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The beneficial waist circumference reduction effect associated with GLP-1RAs observed in our analysis was consistent with relevant trials [36,37,42,43]. A study in 299 T2DM patients showed a significant decrease in waist circumference associated with exenatide accompanied by significant weight loss [42].…”
Section: Discussionsupporting
confidence: 89%
“…Another trial in 69 T2DM patients demonstrated the significant reduction of waist circumference in exenatide treatment for 1 year [43]. Several trials indicated significant decrease in waist/hip ratio associated with GLP-1RAs [28,32,37]. Modest reduction in waist circumference has been proved to be clinically meaningful for T2DM patients [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…After excluding duplicates and screening references on the basis of title and abstract, 123 relevant references were identified and examined in full text. Sixty‐seven of these publications fulfilled the inclusion criteria and were included in the analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 67 included RCTs, 18 investigated the efficacy of GLP‐1ra (six examined exenatide , three liraglutide , five lixisenatide , one dulaglutide and three taspoglutide ), 34 examined DPP‐4i (eight sitagliptin , 10 vildagliptin , seven saxagliptin , four alogliptin , five linagliptin ) and 15 researched SGLT‐2i (eight dapagliflozin , four canagliflozin , three empagliflozin ). All included trials were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 RCTs included, none proved to have a low risk of bias for all seven domains (Figure S3). Four studies demonstrated uncertainty regarding random sequence generation and two studies were unclear in methods of allocation concealment . One study was open‐label and one did not specify the manner of blinding participants and personnel .…”
Section: Resultsmentioning
confidence: 99%